HARALD MOTZKI DAN MUSANNAF ABD AL RAZZAQ - Hakim, Lukman (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
Motzki's views on hadith are contained in his work the origins of Islamic Jurispundence Meccan Fiqh before the Classical Schools. Motzki chose Musannaf Abdul Razzaq as his main study, to prove the authenticity of hadith in the first century of Hijriah, with the assumption, when historical data, namely Musannaf Abdul Razzaq is proven to be authentic historical documentation in the first century of Hijriah, then what is in it is a record of various problems. Islamic law, namely in the form of hadiths, indirectly acknowledges their authenticity. This type of research is completely library research (library research) taking data from the literature that has something to do with the research theme. The analysis technique in this paper uses a content analysis model by exploring and analyzing Motzki's thoughts or views on hadith, especially his main study of Musannaf Abdul Razzaq.